Treatment of Growth Hormone Deficiency via Daily Intravascular Injections in a Child with Bleeding Disorder. (18th June 2021) - Tas, Emir; Uzun, Serife E.; Tas, Vildan; Mejia-Otero, Juan D.
Abstract : Objectives . The standard of treatment for pediatric growth hormone deficiency (GHD) is daily subcutaneous recombinant human growth hormone (rhGH) injections. The efficacy of rhGH treatment given as daily intravenous (IV) boluses is not known. Case Presentation . A female with protein C deficiency, a severe bleeding disorder characterized by thrombosis formation, was diagnosed with GHD at age four years. She has been receiving daily protein C infusion through a permanent port since the newborn period. GHD was treated with daily IV rhGH boluses given through the port following protein C infusion. She has reached a growth rate of 12 cm/year and had no side effects. Surprisingly, serum insulin-like growth factor-1 (IGF1) levels did not rise despite an excellent clinical response. Conclusions . IV administration may be an alternative route for GHD treatment in eligible patients with permanent vascular access. A rise in serum IGF1 levels may not be needed to achieve the growth-promoting effect of rhGH.